Review of development and applications of Integrated Flood Analysis System (IFAS) for flood forecasting in insufficiently-gauged catchments - Chow M.F.; Jamil M.M. (Medwell Journals, 2023)
Flooding problem is becoming more frequent, intense and less predictable in the last century as a consequence of changing climate conditions including shifts in precipitation, soil moisture and land uses. Lack of hydrological data and catchment information has becomes great challenges for the local authorities to set up the flood early warning system in many developing countries. Thus, Integrated Flood Analysis System (IFAS) is developed to forecast the flood event in insufficiently gauged catchments. IFAS Software is able to improve the accuracy of lead time of flood forecast and thus reduce the vulnerability to flood disaster. IFAS can automatically collect the geographical data, soil type, land uses and satellite rainfall data to set up the river basin model for flood simulations. This study reviews the development and applications of IFAS at several river basins with different catchment characteristics in Asian countries. Medwell Journals, 2017.